PERSELINGKUHAN DAN KESETIAAN DALAM SINETRON “CATATAN HATI SEORANG ISTRI” (SUATU STUDI ANALISIS KOMUNIKASI KELUARGA DALAM PERSPEKTIF SEMIOTIKA) - Ratnasari, Dwi Ratnasari; Hasyim, Muhammad; Cangara, Hafied (JURNAL ILMU BUDAYA, 2015)
This research aimed to investigate the representations of infidelity and loyalty, and its effects of the actor of the infidelity and loyalty on the communication of an Islamic family as presented in the soap opera―Catatan Hati Seorang Istri‖. The method used in analyzing the soap opera ―Catatan Hati Seorang Istri‖ was descriptive-qualitative with the approach of semiotic theory by Roland Barthes. In semiotic approach,the message communication process experienced two layers of meaning, namely he first layer (denotation or the illustration of the infidelity and loyalty in the opera soap ―Catatan Hati Seorang Istri‖) and thesecond layer (connotation or the concept of infidelity and loyalty). The research results revealed that there were 86 pictures representing the infidelity, 10 pictures representing the loyalty, and 20 picturesrepresenting the effect of the infidelity actor, and 2 pictures representing the effect of the loyalty actor on the family communication in the islamic perspective as represented in the opera soap ―Catatan HatiSeorang Istri‖. Besides, in the opera soap ―Catatan Hati Seorang Istri‖ semiotically, the signs for lying were used to represent infidelity, while the signs of the shalehah women were used to represent loyalty. Inthe opera soap ―Catatan Hati Seorang Istri‖, infidelity and loyalty effects had significant effects on the communication of islamic families.Keyword: infidelity, loyalty, the soap opera, family communication